2006
DOI: 10.1128/mcb.26.3.1142-1155.2006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Hypoxia-Induced Gene Expression in Early Development: In Vitro and In Vivo Analysis of Hypoxia-Inducible Factor 1-Regulated Zebra Fish Insulin-Like Growth Factor Binding Protein 1 Gene Expression

Abstract: Hypoxia triggers the transcription of regulatory genes that promote O 2 delivery and anaerobic metabolism, suppress major energy-requiring processes, and inhibit growth and development in animals ranging from invertebrates to mammals (14,15,40). Hypoxia also influences several human pathological processes, such as tumorigenesis and intrauterine growth restriction (IUGR). The majority of these transcriptional responses to hypoxia are mediated by the hypoxia-inducible factor 1 (HIF-1) complex. HIF-1 is a heterod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 53 publications
4
107
1
Order By: Relevance
“…This difference in temporal expression pattern signifies that the species of the present study can better tolerate short-term hypoxia, up to 72 h without the aid of a high HIF expression. Also, HIF expression pattern suggests that HIF-1 α is involved in the adaptive response to hypoxia in C. mrigala and helps the fish to survive under short-term hypoxia which is in agreement with several earlier studies (Kajimura et al, 2006;Rahman & Thomas, 2007;Rytkonen et al, 2007). It was also observed that the response of HIF-1 α to low environmental oxygen tensions was quite rapid as the expression level increased even at one-hour exposure to 0.5±0.16 mg/L oxygen level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This difference in temporal expression pattern signifies that the species of the present study can better tolerate short-term hypoxia, up to 72 h without the aid of a high HIF expression. Also, HIF expression pattern suggests that HIF-1 α is involved in the adaptive response to hypoxia in C. mrigala and helps the fish to survive under short-term hypoxia which is in agreement with several earlier studies (Kajimura et al, 2006;Rahman & Thomas, 2007;Rytkonen et al, 2007). It was also observed that the response of HIF-1 α to low environmental oxygen tensions was quite rapid as the expression level increased even at one-hour exposure to 0.5±0.16 mg/L oxygen level.…”
Section: Discussionsupporting
confidence: 91%
“…HIF-1 is a heterodimeric transcription factor formed by the association of a constitutively expressed beta subunit and an inducible alpha subunit, which is rapidly degraded in the presence of oxygen level (Wang & Semenza, 1995). Furthermore, the metabolic and haematological responses during hypoxia are mediated by HIF, which is well studied in several fish species (Kajimura, Aida, & Duan, 2006;Rahman & Thomas, 2007;Rytkonen, Vuori, Primmer, & Nikinmaa, 2007;Terova et al, 2008). However, the time of exposure to hypoxia and its intensity determine the threshold and magnitude of these responses, which is critical to enable the survival of the fish in the hypoxic water.…”
Section: Introductionmentioning
confidence: 99%
“…However, in mammalian hepatocyte culture, hypoxia directly increases hepatocyte IGFBP-1 mRNA levels (Popovici et al 2001, Scharf et al 2005. Further, the zebrafish IGFBP-1 promoter contains a functional hypoxia-response element, indicating that cellular pathways for direct hypoxia induction of IGFBP-1 exist in fishes (Kajimura et al 2006). A 21 kDA IGFBP increased during gradual seawater adaptation in rainbow trout; however, cortisol increased only slightly and transiently (Shepherd et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…However, until recently, definitive identification of these proteins has been lacking due to the absence of molecular sequence data. Recent studies have shown that liver IGFBP-1 gene transcription is induced by hypoxia in adult gobies (Gillichthyes mirabilis) and zebrafish (Danio reiro) (Gracey et al 2001, Maures & Duan 2002, that the induction of IGFBP-1 partially underlies hypoxiainduced growth retardation in zebrafish embryos (Kajimura et al 2005) and that the zebrafish IGFBP-1 promoter contains a functional hypoxia-response element (Kajimura et al 2006). These findings suggest that both the growth-inhibitory role and the regulation of IGFBP-1 may be highly conserved among vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…The frequent occurrence of functional HREs involving in transcriptional response was observed in the 1kb upstream stream from the transcription start site while more than 70% hypoxia responsive genes were found without undetectable HIF-binding site in proximal promoters of a gene (Benita, 2006). Further, the frequently distributed HREs (5'-RCGTG-3') are functionally activated when its downstream contains an adjacent hypoxia ancillary sequence (HAS) in the space of 7-15 nucleotide (Kajimura et al, 2006;Liu et al, 1995). HRE and HAS are five nucleotide motifs and their consensus patterns and {5'-CA(G|C)(A|G)(T|G|C)-3'}] were reported in several hypoxia-inducible genes in mammals and IGFBP1 gene in fish (Kimura et al, 2001;Kajimura et al, 2006).…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 1580-1586mentioning
confidence: 99%